2018
DOI: 10.3174/ajnr.a5517
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Compressed Sensing Accelerated 3D-FLAIR Sequence for the Detection of MS Plaques at 3T

Abstract: With a compressed sensing factor of 1.3, 3D-FLAIR is 27% faster and preserves diagnostic performance for the detection of MS plaques at 3T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 21 publications
1
30
1
1
Order By: Relevance
“…All ROIs were the same size and had nearly identical positioning between sequences. As reported elsewhere in the literature, 7,11 SNR and CNR were calculated as follows: SNR ϭ SI/SD noise and CNR ϭ (SI lesion Ϫ SI WM )/SD noise , where SI is the average signal intensity of the lesion or white matter and SD noise is the SD of noise.…”
Section: Image Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…All ROIs were the same size and had nearly identical positioning between sequences. As reported elsewhere in the literature, 7,11 SNR and CNR were calculated as follows: SNR ϭ SI/SD noise and CNR ϭ (SI lesion Ϫ SI WM )/SD noise , where SI is the average signal intensity of the lesion or white matter and SD noise is the SD of noise.…”
Section: Image Evaluationmentioning
confidence: 99%
“…Only a small number of studies have investigated the performance of CS-SENSE MR imaging in limited patient populations as it relates to body imaging. 4,5 Very few studies have evaluated CS in brain MR imaging, with the studies performed focusing on the evaluation of multiple sclerosis lesions on T2-FLAIR, 7 brain MR imaging quality assessment in healthy controls, 8 and evaluating achievable acceleration, reconstruction schemes, and artifacts generated from retrospective CS. 9 To date, however, no one has critically evaluated the clinical performance of the integrated CS-SENSE algorithm for MR imaging applied to imaging of the central nervous system, to our knowledge.…”
mentioning
confidence: 99%
“…Furthermore, 3D scans allow for additional acceleration using compressed sensing. 12,13 Figure 1(a) shows sagittally acquired 3D T2, (b) 3D FLAIR, and a combination of the two called FLAIR 2 ( FLAIR square ) 14 in Figure 1(c) from a 3 Tesla (3 T) system using an eight-channel head coil and parallel imaging along the left–right and anterior–posterior directions. For comparison, Figure 1(d) shows a 3D FLAIR in a different patient acquired on a current 3 T system equipped with a 32-channel head coil, using a combination of parallel imaging 11 and compressed sensing.…”
Section: General Advantages Of 3d-mri Vs 2d-mrimentioning
confidence: 99%
“…Two potential alternatives to DIR are FLAIR 2 (discussed below), 13 and phase-sensitive inversion recovery (PSIR). Several recent studies showed that PSIR outperforms DIR in terms of total number of cortical lesions detected.…”
Section: Advanced Sequencesmentioning
confidence: 99%
“…Third, at this point this approach is not intended to be used as part of a routine clinical study, but rather as a research tool for investigating the hippocampus or other brain structures requiring high resolution in all three dimensions. Though, combining this approach with other highly accelerated MRI acquisition techniques, such as CAIPI imaging ( Breuer et al, 2006 ; Bilgic et al, 2015 ) (Controlled Aliasing in Parallel Imaging Results in Higher Acceleration), other forms of simultaneous multi-slice imaging ( Barth et al, 2016 ), or compressed sensing ( Lustig et al, 2007 ; Toledano-Massiah et al, 2018 ) for example, may further compress the total study time to something reasonable for a research protocol. In any case, we want to be very clear that this approach is best suited for applications that place a premium on hippocampal internal architecture clarity and can justify investing significant scanner time to obtain high resolution hippocampal images and is not intended to be used in routine clinical scans.…”
Section: Discussionmentioning
confidence: 99%